Determination of the Optimum Conditions for Extracting Polyphenol Ox-idase and Laccase Enzymes From Malva Parviflora and Their Role in The Decolorization of Some Dyes - AL-Sa'ady, Ali Jabbar R.; Hilal, Majid Hameed (Iraqi Journal of Science, 2020)
The current work was undertaken to obtain the crude extract of PPO and laccase enzyme from the leaves of Malva parviflora. All leaves were washed with tap water, then the extraction was performed to acquire the crude extract’s enzymes. One gram of Malva parviflora leaves was homogenized in various volumes of distilled water (1:10, 1:5, and 1:2 w: v). The results showed that polyphenol oxidase and laccase with a ratio of 1:10 (w:v) gave the highest specific activity of 112.3 with 0.394 U/mg proteins. In addition, Malva parviflora leaves were homogenized with several types of buffers with two concentration (0.2 and 0.1 M) for PPO and laccase extraction. These buffers were potassium phosphate (pH 7.0), Tris-HCl (pH 8.0), and sodium acetate (pH 6.0). The results showed that sodium acetate (0.2 M, pH 6) was the best extraction buffer for PPO and laccase with specific activity values of 206.8 and 1.8 U/mg, respectively. Different times for PPO and laccase extraction were determined and the better time was found to be after five minutes, with specific activity values of 251.9 and 1.876 U/mg, respectively, while after 2 and 10 minutes the specific activity values of the enzymes were significantly decreased. Decolorization efficiency of different dyes by the enzyme mixture (PPO and laccase) was determined. It was found that nine dyes (Neutral red, Toluidin blue, Safranin, Crystal violet, Methylene blue, Blood, Phenol red, Henna, and Acridine orange) were altered in their absorbance after incubation with the enzyme mixture for a limited time period.